Validity and reliability of a four-tier diagnostic test on the periodicity of the elements - Parlan, Parlan; Rahmawati, Indah (Indonesian Journal of Science and Mathematics Education, 2025)
This research aims to develop and validate a four-tier diagnostic test to identify high school students’ misconceptions on periodicity of the elements (FTDT-PE). The six-stage development models applied in this process include: (1) mapping concept;  (2) testing and interviewing; (3) defining students' unscientific ideas; (4) developing the prototype FTDT-PE; (5) validating the prototype; and (6) refining the final FTDT-PE. Two chemistry education experts validated the prototype to assess its content, language, and applicability aspects. A pilot project was conducted to assess the test's validity and reliability. The test's content validity is very high, with an average score of 81.58%. Meanwhile, the pilot project results showed that the difficulty level items are in the moderate range, while the discrimination index and distractor effectiveness are good. The reliabilities of answer (A), reason (R), and both tiers (B) are 0.824, 0.841, and 0.875, respectively, all of which are very high. Overall, the FTDT-PE is valid and reliable and is used to diagnose students' misconceptions. Its implication is that the FTDT-PE can serve as a diagnostic tool that strengthens instructional decision-making and enhances the effectiveness of chemistry learning.